PELATIHAN WORK LIFE BALANCE UNTUK STRES KERJA PADA PERAWAT WANITA - Briliani, Afifah Tiara; Husna, Aftina Nurul (Universitas Islam Indonesia, 2024)
Work stress is a common issue experienced by nurses, particularly married female nurses. Literature suggests that work-life balance enhancement can mitigate work stress. This study aims to assess the effectiveness of outsourcing-based work-life balance training in reducing job stress among married female nurses. A quasi-experimental one-group pretest-posttest design was conducted with 10 married female nurses. Data were collected using psychological scales (pretest and posttest), daily journal entries, follow-up interviews, and post-training evaluations. Data were analyzed using paired sample t-tests with IBM SPSS Statistics 25. The data analysis showed a significant result (t(9) = 3.929, p < 0.05, 95% CI = 2.885-10.715), indicating that work-life balance training is effective in reducing job stress among married female nurses.